2002
DOI: 10.1536/jhj.43.93
|View full text |Cite
|
Sign up to set email alerts
|

<b>Levels of Soluble E-selectin and ICAM-1 in the Coronary Circulation of Patients with Stable Coronary Artery Disease</b>

Abstract: SUMMARYThe recruitment of circulating leukocytes to atherosclerotic sites is mediated by a family of adhesion molecules.The objective of the present study was to evaluate the relationship between circulating adhesion molecule levels in the coronary circulation and the severity of coronary atherosclerosis in patients with stable coronary artery disease.The subjects were 79 patients undergoing coronary angiography. According to the severity of coronary atherosclerosis as assessed by the Gensini Score (GS) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…However, only a few studies have addressed a possible correlation of such markers with degree of stenosis or types of lesions seen in angiography. Oishi et al [4] reported that E-selectin is elevated in early stages of stenosis but not in advanced stenosis while conversely ICAM-1 was elevated in advanced stenosis; but Nasuno et al [5] could not confirm the findings on ICAM-1 and suggested that elevated E-selectin reflected systemic rather than coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, only a few studies have addressed a possible correlation of such markers with degree of stenosis or types of lesions seen in angiography. Oishi et al [4] reported that E-selectin is elevated in early stages of stenosis but not in advanced stenosis while conversely ICAM-1 was elevated in advanced stenosis; but Nasuno et al [5] could not confirm the findings on ICAM-1 and suggested that elevated E-selectin reflected systemic rather than coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 94%
“…However, the clinical significance and specificity of those methods remain controversial and no consensus has been reached on which should be adopted for routine clinical assessment of endothelial status in CAD. Oishi et al [4] reported a weak but significant correlation between elevated E-selectin or ICAM and the degree of stenosis of coronary lesions, but this was not confirmed in another study [5]. Katristsis et al [6] reported that elevated C-reactive protein (CRP) was associated with high-risk angiographic lesions (such as irregular lesions, eccentric location, or presence of thrombus), whereas others failed to find such a correlation.…”
Section: Introductionmentioning
confidence: 99%
“…Critical events in the initiation of the vascular inflammatory disease are the adhesion of leukocytes to the dysfunctional and injured endothelium and the penetration of these cells into the vessel wall to generate foam cells. Mechanistic studies show that transcriptional activation of adhesion molecules, including P-selectin, E-selectin, vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), and platelet endothelial cell adhesion molecule (PECAM), [5][6][7] by nuclear factor-B (NF-B) 8,9 plays a pivotal role in the process of cell-cell adhesion. NF-B is activated by oxidative stress, which can be caused by reactive oxygen species (ROS) and reactive nitrogen species generated in free radical reactions from products of enzymes (NADPH oxidases and nitric oxide [NO] synthases [NOSs]) present in the vascular endothelium and smooth muscle.…”
mentioning
confidence: 99%
“…In patients with stable CAD, plasma sEsel levels appear to reflect the severity and cumulative nature of systemic risk factors rather than coronary atherosclerosis per se (27). Moreover, the exact origins of CECs (arterial versus venous, coronary versus peripheral release), their mechanisms of detachment, and potential transcapillary passage have not been fully established.…”
Section: Discussionmentioning
confidence: 99%